Sepsis and the Risks of Long-Term Renal Adverse Outcomes in Patients With Chronic Kidney Disease - Ou, Shuo-Ming; Lee, Kuo-Hua; Tsai, Ming-Tsun; Tseng, Wei-Cheng; Chu, Yuan-Chia; Tarng, Der-Cherng (Frontiers in Medicine, 2022)
Background: Sepsis is known to cause renal function fluctuations during hospitalization, but whether these patients discharged from sepsis were still at greater risks of long-term renal adverse outcomes remains unknown. Methods: From 2011 to 2018, we included 112,628 chronic kidney disease (CKD) patients aged ≥ 20 years. The CKD patients were further divided into 11,661 sepsis group and 100,967 nonsepsis group. The following outcome of interests were included: all-cause mortality, readmission for acute kidney injury (AKI), eGFR decline ≥ 50% or doubling of serum creatinine and end-stage renal disease (ESRD). Results: After propensity score matching, the sepsis group was at higher risks of all-cause mortality (hazard ratio [HR] 1.39, 95% conﬁdence interval [95% CI], 1.31 to 1.47), readmission for acute kidney injury (HR 1.67, 95% CI 1.58 to 1.76), eGFR decline ≥ 50% or doubling of serum creatinine (HR 3.34, 95% CI 2.78 to 4.01) and end-stage renal disease (HR 1.43, 95% CI 1.34 to 1.53) than nonsepsis group. Conclusions: Our study found that CKD patients discharged from hospitalization for sepsis have higher risks of subsequent renal adverse events.